The Labor Force Decision of Married Female Teachers: A Comment - Baqueiro, Armando J.; Breen, James J.; Mead, David E.; Wise, Donald E. (The Review of Economics and Statistics, 1976)
Armando J. Baqueiro, James J. Breen, David E. Mead, Donald E. Wise, The Labor Force Decision of Married Female Teachers: A Comment, The Review of Economics and Statistics, Vol. 58, No. 2 (May, 1976), pp. 241-244